Plant extracts and phytochemicals targeting Alzheimer’s through acetylcholinesterase inhibition - Deepa A V; Dennis Thomas T (Exploration of Neuroscience)
Alzheimer’s disease (AD) is a progressive neurodegenerative disease and the most common type of dementia, characterized by cognitive decline in later years of life. Among various hypotheses explaining AD pathology, the cholinergic hypothesis is one of the most studied. Though there are Food and Drug Administration (FDA) approved drugs (donepezil, galantamine, rivastigmine and tacrine) for AD treatment, their adverse effects make it urgent to develop new drugs with minimal side effects. This review focuses on the acetylcholinesterase (AChE) inhibitory potential of plant extracts and phytochemicals that could aid in preventing and mitigating AD. From the literature search, extracts of 28 species were found to have strong inhibition against AChE, with IC50 values ranging from 0.08 μg/mL to 10.0 μg/mL. The highest number of species with AChE inhibition belongs to the Amaryllidacea family, followed by Fabaceae, Lycopodiaceae, Amaranthaceae and Anacardiaceae. Several phytochemicals, including alkaloids, terpenoids and phenolics, show a multitarget approach in AD therapy, exhibiting more than one of the following activities such as inhibition of AChE, butyrylcholinesterase (BuChE), MAO-A, beta site amyloid precursor protein cleaving enzyme 1 (BACE-1), β-amyloid (Aβ) aggregation, tau phosphorylation, and an ability to cross blood-brain barrier (BBB). With a multitarget approach and minimal side effects, they could revolutionise the treatment of AD. Many phytochemicals and their derivatives are under clinical and pre-clinical trials, potentially serving as prospective therapeutic drug candidates for treating AD. This review briefly discusses the findings and advances in knowledge about plant-derived bioactive compounds as potential new drugs acting as AChE inhibitors.